Markup and productivity of exporters and importers - Cecília Hornok; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2015)
This paper studies the relationship between firm markups and importing intermediate inputs and exporting using detailed firm-level data from Hungary in 1995-2003. We estimate production functions structurally to obtain firm-year-level productivity and markup estimates. We find that importing intermediate inputs is associated with large markup premium, while the exporter markup premium is nonexistent when we control for the importer status. We interpret our results in a simple theoretical framework, where firms lower their markup when exporting to more competitive foreign markets and where importing intermediate inputs leads to higher-quality products.
Keywords: D22; D24; F14; L11; L60; 330; markups; exporting; importing; detailed trade data; Hungary